Primary Healthcare and Maternal Mortality in Selected Areas in Rivers State, Nigeria - Maduawuchi, Elem (NIU Journal of Social Sciences, 2020)
The study focused on the effectiveness of Primary Health Care to reduce maternal mortality in selected areas in Rivers State from 2001-2010. The work observed that primary Health Care is an attempt to address health challenges of low income majority. Given this government did not only establish more health centers but introduced free medicals services among other instruments. In spite of these, most pregnant women patronize Traditional Birth Attendants during delivery. The work is guarded by three hypotheses, system theory was adopted for the work, Survey research design was used. A sample of 400 was drawn from a population of 2,039,040 using Taro Yamane formula but 365 questionnaires were retrieved, this became the sample size. Primary sources and secondary sources of data were used. The hypotheses were analyzed using Chi-Square and student T-Test. Deductions from the analysis shows a rejection of the null hypotheses but maternal mortality reduced due to pregnant women high patronage of antenatal and post natal services in the health centres among other reasons. The work recommended integrative approach involving home base health workers from primary health care centres and Traditional Birth Attendants, women empowerment, compulsory primary and secondary education with bias in health education and maternal education, more employment of health personnel, among others. Keywords: Primary Health Care, Maternal Mortality.